Hyperspectral data of IODP Hole389-M0099B - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Hyperspectral data from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs) acquired by TheiaX GmbH during the onshore phase of the expedition, which was held between 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. Acquisition of hyperspectral image data took place on all Archive halves and selected core slabs using a SisuROCK drill-core scanner (Spectral Imaging Ltd., Oulu, Finland) equipped with an AisaFENIX hyperspectral sensor to cover the visible and near-infrared (VNIR) as well as short-wave infrared (SWIR) regions of the electromagnetically spectrum. Relative abundance of water, dolomite, aragonite, clay and iron-silicates were logged in 1-cm intervals downcore for each core section and mineral domains interpreted from these results. Further, spectral indices-based carbonate maps were produced for each scanned section. For further methodological information and processing procedures see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025